The Effect of Different Doses of Botulinum Toxin on Masseter Muscle in Patients with Bruxism. - Kawa F. Dizaye; Sarezh Jamal Jalal (Erbil Dental Journal, 2022)
Background and Objectives: Botulinum toxin type A is produced by clostridium botulinum. It acts by inhibiting the release of acetylcholine from cholinergic neurons. Botulinum toxin has been used for management of bruxism, which is a parafunctional disorder and characterized by clenching or grinding of the teeth or both. This study aimed to find out the effect of two different doses of injecting botulinum neurotoxin in masseter muscle in a patient with bruxism. Materials and Methods: A prospective clinical open trial study was conducted from November 2018 to November 2019. Thirty patients, aged 20-45 years, with bruxism were subjected to injection of two different doses of botulinum toxin in masseter muscle. Patients were divided into two equal groups. The first group included 15 patients treated by 18 units of botulinum toxin, 9 units for each side and the second group included 15 patients treated by 24 units of botulinum toxin 12 unit for each side. Parameters, as visual analogue scale (VAS), Bite force, patient’s evaluation of lower facial slimming were recorded for each patient before and after the injections of botulinum neurotoxin at 2 weeks, 4 weeks and 3 months. Results: The study showed a significant reduction in VAS, bite force and patient's evaluation of facial slimming for both groups after 2 weeks, 4 weeks and 3 months of follow up (P < 0.05) with no significant differences in both group doses.